The Effects of Coconut Skim Milk and Coco-Dairy Milk Blend on the Nutritional Status of Schoolchildren - Imelda A. Agdeppa; Jezreel Ann T. Zamora (Journal of Nutrition and Metabolism)
Milk feeding can be an effective response to the high prevalence of child undernutrition as it provides significant amounts of nutrients. This study investigated and compared the effects of coconut skim milk (CocoM) and coco-dairy milk blend (CDMB) to cow’s milk (CM) on improving the nutritional status of Filipino schoolchildren. The study followed a randomized, double-blind, controlled, parallel-group design. A total of 444 underweight/stunted schoolchildren aged 6.0–8.4 years old enrolled in Guadalupe Elementary School in Cebu City, Philippines, have participated. The participants were randomly allocated into three groups, that is, CocoM, CDMB, and CM, in which the milk products were packed in 200 ml color and number-coded bottles given for 95 days. The bottles were similar in form and shape, and the only differentiating factors were the code and color. Weight and height were measured using standard techniques. Nutritional indices such as weight-for-age z-score (WAZ), height-for-age z-score (HAZ), and BMI-for-age z-score (BAZ) were measured using the WHO Child Growth Standards (CGS), and the acceptability test was measured using the 5-point facial hedonic scale. The study found that the mean WAZ and BAZ had significantly increased from baseline to endpoint across all groups. Moreover, the prevalence of underweight has also significantly declined from baseline to endpoint in all groups, and the prevalence of stunting significantly declined from baseline to endpoint in the CocoM group only. Lastly, the three milk products were rated as generally acceptable. Overall, the findings indicate that coconut milk consumption could be beneficial for improving a child’s WAZ and BAZ, as well as improving the nutritional status of underweight and stunted schoolchildren. CocoM and CDMB were found to be equally beneficial to child nutrition as cow’s milk. Hence, the present study suggests that CocoM and CDMB could be also provided in school-based feeding programs with the aim of targeting child undernutrition.